2020 IEEE 92nd Vehicular Technology Conference (VTC2020-Fall) 2020
DOI: 10.1109/vtc2020-fall49728.2020.9348746
|View full text |Cite
|
Sign up to set email alerts
|

Network Anomaly Detection in Cars based on Time-Sensitive Ingress Control

Abstract: Connected cars are vulnerable to cyber attacks. Security challenges arise from vehicular management uplinks, from signaling with roadside units or nearby cars, as well as from common Internet services. Major threats arrive from bogus traffic that enters the in-car backbone, which will comprise of Ethernet technologies in the near future. Various security techniques from different areas and layers are under discussion to protect future vehicles. In this paper, we show how Per-Stream Filtering and Policing of IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…2. The IVN fields and their subjects in the reviewed works Field Paper(s) Subjects Requirements of automotive TSN [6], [11], [12] List of requirements for future IVN processing platforms [13], [14] Integrate TSN with SDN with security [15] NDN [16] Graceful degradation for real-time autonomous vehicle applications [17] Improve the accuracy of the canvas [10] Reducing latency by porting it to Xronos [18] TSN-5G heterogeneous networks [19] HPVUs security [20] OTT Ethernet algorithm [21] Ethernet backbone with Zone based architecture [22] iDriving [45], [46] TSN PSFP, Protection of the TSN automotive Ethernet Security protocols for IVN [23], [24], [30], [35], [39] Review of blockchain and security attributes of IVN [34] IPSEC [36] Extensions to the SOME/IP protocol for securing SOME/IP service discovery [37] CANFD [25]- [29], [33], [38] Confidentiality, authentication, integrity [30]- [33] Blockchain in IVN [40] Structure-aware CAN Fuzzing procedure [41] Mitigations against an underactuated USV Intrusions detection systems for IVN [29], [42], [44], [47], [48], [53] Intrusion Detection Systems [49], …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The IVN fields and their subjects in the reviewed works Field Paper(s) Subjects Requirements of automotive TSN [6], [11], [12] List of requirements for future IVN processing platforms [13], [14] Integrate TSN with SDN with security [15] NDN [16] Graceful degradation for real-time autonomous vehicle applications [17] Improve the accuracy of the canvas [10] Reducing latency by porting it to Xronos [18] TSN-5G heterogeneous networks [19] HPVUs security [20] OTT Ethernet algorithm [21] Ethernet backbone with Zone based architecture [22] iDriving [45], [46] TSN PSFP, Protection of the TSN automotive Ethernet Security protocols for IVN [23], [24], [30], [35], [39] Review of blockchain and security attributes of IVN [34] IPSEC [36] Extensions to the SOME/IP protocol for securing SOME/IP service discovery [37] CANFD [25]- [29], [33], [38] Confidentiality, authentication, integrity [30]- [33] Blockchain in IVN [40] Structure-aware CAN Fuzzing procedure [41] Mitigations against an underactuated USV Intrusions detection systems for IVN [29], [42], [44], [47], [48], [53] Intrusion Detection Systems [49], …”
Section: Resultsmentioning
confidence: 99%
“…The TSN per-stream filtering and policing (PSFP) can be utilized as a fundamental technology for detecting malicious traffic flows in vehicles, and in this manner provide network anomaly detectors services as explained by Meyer et al [45]. They evaluated the detection systems based on backbone topology derived from a real vehicle and their traffic classification; their results showed that the detection accuracy depends on some factors such as: the corruption layer, the traffic type.…”
Section: Intrusions Detection Systems For Ivnmentioning
confidence: 99%
“…Emphasizing that the original specification for CAN lacks a central monitoring mechanism, Häckel et al [45] offers an architecture integrating TSN and SDN, in which all real-time traffic transmitted in an in-vehicle network is centrally monitored without increasing the network delay in order to prevent malicious traffic. Meyer et al [46] performs anomaly detection by using TSN and SDN technologies together in an invehicle communication network, which relies on the filtering capabilities of Per-Stream Filtering and Policing (PSFP) specified [47] proposes an anomaly detection system for invehicle networks with TSN support relying on PSFP specified in 802.1Qci in order to block the messages exceeding a customized maximum service data unit size. The authors experimentally show that the proposed system successfully identifies four different abnormal traffic events in relation with DoS attacks.…”
Section: Defense Strategies For In-vehicle Networkmentioning
confidence: 99%
“…Anomaly detection can identify ongoing attacks in the network [39], e.g., using machine learning algorithms to detect anomalies on the CAN bus [40]. In previous work [41], we Fig. 2: Integrated network architecture of TSN and SDN.…”
Section: In-vehicle Network Securitymentioning
confidence: 99%